The Role of Joseph de Finance’s Axiological Concept in Opening Youth to the World of Values - Oľga Gavendová (Seminare)
Research and common experience confirm that value orientation of young people has changed fundamentally. Material values have come to the fore and young people do not seem to recognize higher values at all. The subject of the study is the phenomenon of blindness and deafness to higher values. The fact was pointed out by Joseph de Finance, who formulated an axiological conception that offers a solution to this problem. Every human being needs basic values, both material and spiritual, that enable his or her integral development. Each group of values corresponds to certain needs resulting from human nature. However, children or young people often remain attached to material values while they fail to open up to higher values, especially moral ones. The educator must use kairos and help children to take this step. The educator helps those who are blind to certain values to find other similar values that they can recognize. Teachers must help young people to tune in to the wavelength of certain values so they can hear them. The realization of the moral value is of crucial importance since it is through that value that people can develop integrally and find happiness.